Dodder-transmitted mobile systemic signals activate a salt-stress response characterized by a transcriptome change in Citrus sinensis - Duan, Shuo; Xu, Zhou; Li, Xin-Yu; Liao, Ping; Qin, Hong-Kun; Mao, Ya-Ping; Dai, Wen-Shan; Ma, Hai-Jie; Bao, Min-Li (Frontiers in Plant Science, 2022)
Citrus is an essential horticultural fruit whose yield and quality are affected by salinity all over the world. The recognition and adaptive regulation of citrus against salt stress are important areas for cultivar improvement, but the vascular system signal transduction mechanism of the plant response to salt stress remains elusive. In this study, we constructed a dodder (Cuscuta spp.) linked Hamlin sweet orange (Citrus sinensis) plant community in which deliver a vascular signal through the dodder in response to salt stress. RNA-seq technology was used to analyze the gene expression profile of citrus leaves after salt treatment. The results showed that a vascular signal was transmitted to a dodder-linked host plant, triggering a transcriptional response to salt stress. However, the phenotypic and transudative ability of the dodder changed after 24 h. The salt treatment group (Group S) and the dodder-linked group (Group D) respectively contained 1,472 and 557 differentially expressed genes (DEGs). 454 of which were common to both groups. The results of our analysis revealed that the gene expression categories in Group D represented a highly consistent trend compared to the group S plants, indicating that the dodder-bridged vascular signals activated the stress-response of citrus leaves for transcriptomic reconfiguration. The KEGG pathway database and an analysis of key drivers revealed that phenylpropanoid biosynthesis, photosynthesis-antenna proteins, starch and sucrose metabolism, plant hormone signal transduction, circadian rhythm, and MAPK signaling pathways were significantly enriched as the critical genes during salt stress. A systemic signal in the dodder-bridged host significantly regulated abiotic stress-related secondary metabolic pathways, including those for phenylpropanoids, lignin, and lignans. The physiological indexes of photosynthetic intensity, respiration, and attractiveness among communities supported the transcriptional changes. Thus, our results indicate that salt stress-induced vascular system signals can be transmitted through the vascular system of a dodder linking citrus plants, revealing the genetic regulation and physiological changes of citrus leaves responding to plant stress signal transmission.